Children with Amalgam Dental Restorations Have Significantly Elevated Blood and Urine Mercury Levels. (28th August 2021) - Yin, Lei; Lin, Simon; Summers, Anne O; Roper, Van; Campen, Matthew J; Yu, Xiaozhong
Abstract: Human exposure to organic mercury (Hg) as methylmercury (MeHg) from seafood consumption is widely considered a health risk because pure methylmercury is extremely neurotoxic. In contrast, the clinical significance of Hg exposure from amalgam (AMG) dental restorations, the only other major nonoccupational source of Hg exposure, has long been debated. Here, we examined data from the two most recent National Health and Nutrition Examination Surveys (NHANES) on 14 181 subjects to assess the contributions of seafood consumption versus AMG to blood total mercury (THg), inorganic mercury (IHg), and methyl mercury (MeHg) and to urine creatinine corrected mercury (UTHg). All subjects were also classified as to their self-reported qualitative consumption of seafood (59% fish and 44% shellfish). Subjects with restorations were grouped into three groups (0) those without AMG (64.4%), (1) those with 1–5 dental AMG restorations (19.7%), (2) those with more than five AMG (16%). Seafood consumption increased total mercury in urine (UTHg) and total mercury (THg) and methyl mercury (MeHg) in blood, but unlike AMG, seafood did not increase blood inorganic mercury (IHg). Using stratified covariate (ANOVA) and multivariate (GLM) analyses revealed a strong correlation of blood (THg and IHg) and urine (UTHg) levels with the number of AMGs. In a subpopulation without fish consumption, having more than five AMG restorations raised blood THg (103%), IHg (221%), and urine UTHg (221%) over the group without AMG. The most striking difference was noted in classification by age: subjects under 6 years old with more than five AMG restorations had the highest blood IHg and urine UTHg among all age groups. Elevation of bivalent IHg on a large scale in children warrants urgent in-depth risk assessment with specific attention to genetic- and gender-associated vulnerabilities.